2014
DOI: 10.1515/bmc-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin: recent developments and novel roles in health and disease

Abstract: Over 80 years has passed since the discovery of substance P (SP), and a variety of peptides of the tachykinin (TK) family have been found and investigated. SP, neurokinin A (NKA), and neurokinin B (NKB) are representative peptides in mammalian species. SP and NKA are major excitatory neurotransmitters in the peripheral nervous system, while NKB is primarily involved in the central nervous system (CNS). Moreover, TK peptides play roles not only as neurotransmitters but also as local factors and are involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 148 publications
(169 reference statements)
1
43
0
Order By: Relevance
“…The major tachykinins (NKA, NKB, and SP) and CGRP are distributed throughout the peripheral and central nervous system 74,75 . Expression of signaling molecules, for example, in the trigeminovascular system 10,74,76,77 indicate a potential role in the migraine and CH pathophysiology. SP is expressed in the human trigeminal ganglia, 78 but clinical trials of SP blockers revealed no effect in acute migraine 79,80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major tachykinins (NKA, NKB, and SP) and CGRP are distributed throughout the peripheral and central nervous system 74,75 . Expression of signaling molecules, for example, in the trigeminovascular system 10,74,76,77 indicate a potential role in the migraine and CH pathophysiology. SP is expressed in the human trigeminal ganglia, 78 but clinical trials of SP blockers revealed no effect in acute migraine 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no studies with focus on NKB for both primary headache disorders were identified. One explanation could be that NKB mainly seems to be involved in functions in the central nervous system, in contrast to SP and NKA which are considered key excitatory neurotransmitters in the peripheral nervous system 74,81 . Mapping signaling molecules (including others not investigated in this SR‐MA, for example, glutamate and gamma‐aminobutyric acid to investigate excitatory‐inhibitory balance) to the peripheral and central nervous system might, therefore, be beneficial prior to future selection of signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 NKA and tachykinins receptors are involved in central and peripheral regulation of various physiological functions. 5,6 The mediating role of neurokinins in breathing has been disclosed by Bongianni et al, 2 who showed that exogenous agonists acting on receptors within the respiratory network control mainly the frequency of inspiratory bursts. Microinjection of NKA into the pre-BötC region in the rabbit evoked increases in respiratory frequency.…”
Section: And Nk 2 Receptors In Cardiovascular and Respiratory Effectsmentioning
confidence: 99%
“…NKA acts as a full agonist on the three TK receptors although preferentially binds to the neurokinin NK 2 receptor . NKA and tachykinins receptors are involved in central and peripheral regulation of various physiological functions . The mediating role of neurokinins in breathing has been disclosed by Bongianni et al., who showed that exogenous agonists acting on receptors within the respiratory network control mainly the frequency of inspiratory bursts.…”
Section: Introductionmentioning
confidence: 99%
“…Tachykinins comprise a family of neuropeptides that are widely distributed in both central and peripheral nervous systems . Notably, the 3 classic tachykinins, SP, neurokinin A, and neurokinin B, have been implicated in the pathogenesis of airway diseases .…”
mentioning
confidence: 99%